Ethics-testing an eating disorder recovery memoir: A pre-publication experiment - Troscianko, E; Carney, J; Riestra Camacho, R (University of Oxford, 2024)
The dataset was created as part of a pre-publication study conducted between 2021 and 2023. It comprises 1) the pre- and post-reading scores for the two standardized measures used in the study (the Eating Disorder Examination Questionnaire [EDE-Q] and the Anorexia Nervosa Stages of Change Questionnaire [ANSOCQ] and 2) details of the qualitative analysis of the free-text data, including the data excerpts and their categorization, in a) .xlsx, b) .csv, and c) .docx formats. NB: This dataset supersedes the earlier version at https://ora.ox.ac.uk/objects/uuid:b1d2fe55-6515-404b-991e-e524903076c2 (DOI: http://dx.doi.org/10.5287/ora-xrgnx0oon).